Diagnostic utility of the Active Compression Test for the superior labrum anterior posterior tear: A systematic review. (October 2019) - Davis, Cody; Immormino, Jenna; Higgins, Brendan M; Clark, Kyle; Engebose, Samuel; Garcia, Alessandra N; Cook, Chad E
Background: The Active Compression Test has been proposed to have high diagnostic accuracy for superior labrum anterior to posterior tears. The aim of this systematic review was to compile the available evidence for this test and evaluate its diagnostic accuracy. Methods: The databases PubMed, Embase, Cochrane, CINAHL, and SCOPUS were searched for case control, diagnostic studies that evaluated the Active Compression Test between 1999 (date of test introduction) and February 2018. Two independent review authors screened the search results, assessed the risk of bias using QUADAS-2, and extracted the data. Results: Eighteen studies (pooled sample = 3091) were included in this review. Twelve out of 18 studies either had high or unclear risk of bias (66.6%). Results from the pooled analysis of all 18 studies provided that the Active Compression Test is more sensitive (71.5: 95% CI = 68.8, 74.0) than specific (51.9: 95% CI = 50.7, 53.1) and only marginally influenced posttest probability from a pretest probability of 31.7–40.72% with a positive finding and a pretest probability of 31.7–20.33% with a negative finding. Discussion: The Active Compression Test has both limited screening and confirmation ability; therefore, we do not advocate for its use in clinical decision making.